The Brazilian health system: highlighting the primary health care reform (Italian Journal of Public Health, 2010)
This paper aims to describe the health system reform in Brazil, highlight the primary health care reform and the development of the Family Health Program, as well as explore future directions based on the current situation. The paper’s first section provides an overview of the Brazilian Health System and a brief historical perspective of the health system reform. It sets out the principles of the health system based on its legal framework and analyses how these principles have been implemented. At the end of the first section, an overview of financial issues is provided. The second section focuses on the primary care reform and the Family Health Program. It describes the program’s structural and innovative process characteristics. It further describes some of the outcomes and impacts already documented in the literature. Finally, the paper explores challenges to the health system and the program’s sustainability
Keywords: Brazil; health system; primary health care reform; family health program